Lactylation: a promising therapeutic target in ischemia-reperfusion injury management - Fei-xiang Wang; Guo Mu; Zi-hang Yu; Zu-an Shi; Xue-xin Li; Xin Fan; Ye Chen; Jun Zhou (Cell Death Discovery)
Abstract Ischemia-reperfusion injury (IRI) is a critical condition that poses a significant threat to patient safety. The production of lactate increases during the process of IRI, and lactate serves as a crucial indicator for assessing the severity of such injury. Lactylation, a newly discovered post-translational modification in 2019, is induced by lactic acid and predominantly occurs on lysine residues of histone or nonhistone proteins. Extensive studies have demonstrated the pivotal role of lactylation in the pathogenesis and progression of various diseases, including melanoma, myocardial infarction, hepatocellular carcinoma, Alzheimer’s disease, and nonalcoholic fatty liver disease. Additionally, a marked correlation between lactylation and inflammation has been observed. This article provides a comprehensive review of the mechanism underlying lactylation in IRI to establish a theoretical foundation for better understanding the interplay between lactylation and IRI.